Penerapan Teknologi Internet of Things Untuk Meningkatkan Efisiensi Pencarian Tempat Parkir Mobil Di Lingkungan Pusat Perbelanjaan - Calvin Aditama Novrandika, Orlando; Aziz Herlambang, Muhammad; Andrian Prasetyo, Yoga; Pramono (CV. Shofanah Media Berkah, 2024)
This research aims to apply Internet of Things technology to increase the efficiency of finding car parking spaces in shopping center environments. The system developed is expected to provide real-time parking availability information, guide users to suitable parking spaces, and reduce search time significantly. This research method involves web-based system design and prototyping. Parking space vacancy data will be collected via an ultrasonic sensor type HCSR04. And it will be sent from the ESP8266 microcontroller to the parking website. The application of Internet of Things technology to efficiently find parking spaces in shopping center environments is expected to produce positive results. Users will be able to access real-time parking availability information and reduce search time. In addition, the application of this technology is expected to improve user experience and optimize the use of parking spaces in shopping center environments. By combining web-based technology and HCSR04 type ultrasonic sensors, this system can provide an effective solution to increase the efficiency of finding parking spaces in shopping center environments. It is hoped that the positive impact of this research can contribute to the progress and management of the urban environment.